STRUKTUR HIERARKI FEMINISME DALAM KUMPULAN CERPEN JANGAN MAIN-MAIN DENGAN KELAMINMU KARYA DJENAR MAESA AYU - Kulyum, Kulyum (Jurnal Sastra Aksara, 2018)
Women as social and individual beings are created with equal positions and roles with men. The next approach that women are lower than men. But women have their own charm so women become the center of attention of poets. Moreover, short story writing in the world of Indonesian literature has already begun with many female figures. Especially in feminism hierarchy structure in collection of short stories â€Jangan Main-Main dengan Kelaminmuâ€ by Djenar Maesa Ayu. This research was conducted on the basis of knowing the contents of the short stories of women. The formulation of the research problem was feminism hierarchy structure in collection of short stories â€Jangan Main-Main dengan Kelaminmuâ€ by Djenar Maesa Ayu and author's view of the hierarchical structure of feminism through characterization in collection of short storiesby Djenar Maesa Ayu. This study aimed to analyze changes of feminism hierarchy structure in collection of short stories â€Jangan Main-Main dengan Kelaminmuâ€ by Djenar Maesa Ayu and author's view of the hierarchical structure of feminism through characterization in collection of short storiesby Djenar Maesa Ayu. The type of research was qualitative research and the research method consists of data acquisition techniques in the form of documentation, and data processing techniques were reading and note-taking collection of short stories contained in the object of research. Choose short story text, analyze hierarchical structure in short story text, analyze author's viewin collection of short stories â€Jangan Main-Main dengan Kelaminmuâ€ by Djenar Maesa Ayu. The results of this study aimed to describe the female figure in the feminism hierarchy structure that had two groups, namely the upper class feminism hierarchy structure and the lower class feminism hierarchy structure, namely female figures who had different social classes in collection of short stories â€Jangan Main-Main dengan Kelaminmuâ€ by Djenar Maesa Ayu, whereas in the author's view of the feminist hierarchical structure through characterization in a collection of short stories by Djanar Maesa Ayu on female characters who had very strong character and were not afraid of losing what women have.